Avoiding deep pelvic complications using a 'Five‐Step' technique for high submuscular placement of inflatable penile prosthesis reservoirs. (2nd July 2020) - Baumgarten, Adam S.; Kavoussi, Mehraban; VanDyke, Maia E.; Ortiz, Nicolas M.; Khouri, Roger K.; Ward, Ellen E.; Hudak, Steven J.; Morey, Allen F.
Abstract : Objectives: To compare our extended experience with high submuscular (HSM) reservoir placement to traditional space of Retzius (SOR) placement and to present our current, refined 'Five‐Step' technique (FST) for HSM placement. Patients and Methods: Data were retrospectively collected on patients undergoing inflatable penile prosthesis (IPP) placement between January 2009 and June 2019. Re‐operative cases were excluded. Reservoir‐related complications and subsequent revisions were compared between SOR (2009–2012) and HSM reservoir groups (2012–2019). HSM patients were subdivided into two cohorts: 'Initial Technique' (2012–2014) and FST (2014–2019). The refined FST protocol was developed in 2014 to optimise outcomes and includes the following steps: (i) Position and Access; (ii) Develop Lower HSM Pocket; (iii) Develop Upper HSM Pocket; (iv) Reservoir Delivery (fill and fine‐tune); (v) Confirm and Connect. Results: Between January 2009 and June 2019, 733 total IPP procedures (586 HSM, 147 SOR) were performed by a single surgeon at our institution, 561 of which were virgin cases (430 HSM, 131 SOR) and included in this analysis. Overall, surgical revision was required in 10/430 (2.3%) HSM cases (one delayed bowel obstruction, nine herniations) and six of 131 (4.6%) SOR cases (one bladder erosion, two vascular injuries, and three herniations, P = 0.22). When comparing the FST to the Initial Technique, we noted a significant decrease in complications requiring surgical revision ( P = 0.01). Among 133 cases performed with the Initial Technique, seven (5.3%) required surgical revision (one bowel obstruction after placement into the peritoneal cavity, six herniations). Among 297 FST cases, three (1.0%) required revision, all due to herniation. Conclusion: HSM placement of IPP reservoirs is a safe alternative to traditional SOR placement. Major deep pelvic reservoir complications were minimised using our current refined FST.